Bonebeds : genesis, analysis, and paleobiological significance - Rogers, Raymond R.; Eberth, David A.; Fiorillo, Anthony R. (University of Chicago Press, 2007)
The vertebrate fossil record extends back more than 500 million years, and bonebeds--localized concentrations of the skeletal remains of vertebrate animals--help unlock the secrets of this long history. Often spectacularly preserved, bonebeds--both modern and ancient--can reveal more about life histories, ecological associations, and preservation patterns than any single skeleton or bone. For this reason, bonebeds are frequently studied by paleobiologists, geologists, and archeologists seeking to piece together the vertebrate record. Thirteen respected researchers combine their experiences in Boneb.